THE PROBLEMS OF BENEFICIAL DRUG SUPPORT - L. V. Shukil; L. V. Moshkova; E. A. Korzhavych (Фармация и фармакология (Пятигорск))
The monitoring of drug supply availability to the population in the frameworks of state guarantees and timely revelation of problems appeared is one of the most important issues of Russian healthcare. Revelation of prevailing problems connected with consumers while implementing the program of state guarantees concerning drug support on a regional level (Omsk oblast) and modeling the solutions of some of these problems was the purpose of our study. We have used methods of logic, statistic, and clinical and economical analysis in our work. We have revealed the principal problems of beneficial drug supply consumers which are reduction of beneficial drug request, substitution of drug support with monetary compensation. We have made conclusions about the necessity of more active informing of consumers about the consequences of drug supply refusal and the widening of category lists of persons entitled for benefits on a regional level.